Preparation method of high-nickel ternary positive electrode material coated with high-molecular polymer

By forming a polymer coating on the surface of high-nickel ternary positive electrode material, the problems of slow diffusion of lithium ions and poor rate performance at extremely cold temperatures are solved, and the electrochemical performance and capacity retention of the battery are significantly improved.

CN119695085APending Publication Date: 2025-03-25ZHENGZHOU UNIV

Patent Information

Application Number
CN202411892124.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

High-nickel ternary cathode materials exhibit slow diffusion of lithium ions and poor rate performance at extremely cold temperatures, which limits their application at extremely cold temperatures.

Method used

By mixing the polymer with the high-nickel ternary cathode material powder under ultrasound, a uniform surface coating layer is formed, which improves the diffusion rate and electrochemical properties at the lithium ion interface.

Benefits of technology

The rate performance of lithium-ion batteries at extremely cold temperatures was significantly improved, the discharge specific capacity was increased by 4 times at -40℃, and the capacity retention rate reached 78.36% after 300 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695085A_ABST
    Figure CN119695085A_ABST
Patent Text Reader

Abstract

The invention aims to disclose a preparation method of a high-nickel ternary positive electrode material coated with a high-molecular polymer. The preparation method comprises the following steps: (1) mixing and stirring the high-molecular polymer and an organic solvent; (2) slowly adding high-nickel ternary positive electrode material powder in ultrasonic treatment, and continuously performing ultrasonic treatment, so that the ternary positive electrode powder is in full contact with the conductive polymer; (3) heating and stirring by using a magnetic stirrer, and polymerizing; and after the polymerization is completed, washing and filtering, and then carrying out vacuum drying to obtain the high-nickel ternary positive electrode material coated with the high-molecular polymer. The high-stability lithium battery ternary positive electrode material coating is synthesized through the method, the method is simple and effective, a coating layer with the uniform surface is formed, interface ion transmission is improved, the problem that lithium ions are diffused slowly due to the fact that CEI is too thick at the extremely cold temperature is solved, and the electrochemical performance of a battery at the extremely cold temperature is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium battery positive electrode materials, and in particular to a preparation method and application of a high-nickel ternary positive electrode material coated with a high molecular polymer. Background Art

[0002] Lithium metal batteries have high energy density, theoretical specific capacity (3860mAh / g), and minimum electrochemical potential. They are the key to achieving carbon-neutral travel. In the future, they are expected to gradually replace traditional lead-acid batteries and become the main energy storage device for electric vehicles. They are widely used in electric vehicles, mobile power supplies, energy storage systems, etc. The positive electrode material is the main factor restricting the energy density of lithium metal batteries. The NMC532 and NMC622 positive electrode materials currently used on a large scale in the market cannot meet the country's requirements for the energy density of power batteries. Therefore, it is a general trend to use positive electrode materials with higher specific capacity to meet the demand.

[0003] High nickel ternary cathode material LiNi x Mn 1-x-y Co y O2 (NMC) is considered a promising candidate for the next generation of cathode materials due to its high capacity, excellent rate performance and low cost. However, in the fields of aerospace, military industry, electric vehicles, etc., batteries are required to work normally in extremely cold weather. The performance of lithium metal batteries decays rapidly at low temperatures and the discharge capacity is poor, which limits their application at extremely cold temperatures. Studies have shown that under extremely cold temperature conditions, the CEI film formed at the cathode interface is too thick and uniform, which hinders the diffusion of lithium ions, the discharge depth is low, and the charge transfer slows down at low temperatures, the electronic conductivity decreases, the lithium ion diffusion rate decreases, and the charge transfer impedance at the interface increases, which seriously affects the rate performance of the battery at extremely cold temperatures. In response to these problems, the performance of cathode materials at low temperatures can usually be improved by doping and coating methods to improve ion power. However, doping with inorganic materials such as Al2O3 and TiO2 will increase the interface resistance, and the lithium ion diffusion coefficient is low. The surface modification of cathode materials using conductive polymers can effectively increase the diffusion rate at the lithium ion interface, reduce the diffusion impedance at the interface, and improve the performance of lithium-ion batteries at extremely cold temperatures. However, achieving this goal remains a major challenge. Summary of the invention

[0004] In view of the problems existing in the above-mentioned high-nickel ternary positive electrode materials at low temperatures, a method is provided to effectively alleviate the slow diffusion of lithium ions caused by excessive thickness of the CEI film under extremely cold temperature conditions, and effectively improve the rate performance of lithium-ion batteries at extremely cold temperatures, which is of great significance for the application of lithium-ion batteries at extremely cold temperatures.

[0005] The objective of the present invention is achieved through the following technical solutions: A method for preparing a high-nickel ternary positive electrode material coated with a polymer, comprising the following steps: (1) Mixing and stirring the polymer and the organic solvent; (2) Slowly add high nickel ternary cathode material powder in ultrasound and continue ultrasound to ensure that the ternary cathode powder is in full contact with the polymer; (3) Using a magnetic stirrer to heat and stir to carry out polymerization; after the polymerization is completed, washing and filtering are performed, and then vacuum drying is performed to obtain a high-nickel ternary positive electrode material coated with a polymer.

[0006] The organic solvent in step (1) is one of ethanol, hydroxymethane, N-methyl-2-pyrrolidone, N,N-dimethylformamide, isopropanol and the like.

[0007] The high molecular weight polymer in step (1) is one of materials such as polyacrylonitrile, polypyrrole, polyethylene glycol, polyacrylamide, polyacrylic acid and polyacetylene.

[0008] The high nickel ternary positive electrode material in step (2) is LiNi x M 1-x-y Co y O2, wherein M is at least one of Al, Mn, Mg, Ti, and W, and x≥0.8, and 0<y≤1.

[0009] The duration of ultrasound in step (2) is 10-30 minutes.

[0010] In the step (1), the mass of the high molecular weight polymer is 0.5% to 3% of the mass of the organic solution.

[0011] The mass of the high molecular weight polymer in step (2) is 0.5% to 5% of the mass of the high nickel ternary positive electrode material.

[0012] In the step (2), the mass of the high molecular weight polymer is preferably 1.5% to 3% of the mass of the high nickel ternary positive electrode material.

[0013] In the step (3), the heating temperature is 50 to 80° C., the rotation speed of the magnetic stirrer is 400 to 1000 rpm, and the stirring time is 6 to 12 hours.

[0014] The vacuum drying temperature in step (3) is 60 to 120° C., and the vacuum drying time is 10 to 18 hours.

[0015] Compared with the prior art, the present invention has the following advantages and beneficial effects: The method of the present invention synthesizes a lithium battery ternary positive electrode material coating with high stability. The method is simple and effective, forms a uniform surface coating layer, improves interface ion transmission, improves the slow lithium ion diffusion problem caused by excessively thick lower CEI at extremely cold temperatures, and effectively improves the electrochemical performance of the battery at extremely cold temperatures.

[0016] The preparation method of the present invention is simple, low in cost, has low requirements on the equipment and process conditions, has fine particles in the coating layer, has a large specific surface area, has a better coating effect, and is easier to form a uniform and dense coating on the surface of the high-nickel ternary positive electrode material.

[0017] The preparation process of the present invention is different from the prior art. Through ultrasonic operation, the performance improvement effect at extremely cold temperatures is more obvious and the capacity retention rate is also higher.

[0018] The present invention provides a battery assembled from a polymer-coated high-nickel ternary positive electrode material. At 2.7-4.35V, -40°C and 1C discharge rate, the discharge specific capacity is as high as 103.5mAh / g, while that of an uncoated battery is 24.8mAh / g, an increase of 4 times; after 300 cycles, the discharge capacity is still 81.1mAh / g, and the capacity retention rate is 78.36%. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 LiNi without coating and coated with polymer 0.83 Mn 0.05 Co 0.12 The button cell with O2 material as the positive electrode and lithium metal as the negative electrode was tested at 0.1C / 1C and -40℃. Figure 2 Polymer-coated LiNi 0.83 Mn 0.05 Co 0.12 The soft pack battery with O2 material as the positive electrode and lithium metal as the negative electrode was tested at 0.1C / 0.1C and -40℃. Figure 3 LiNi 0.83 Mn 0.05 Co 0.12 O2 is the performance difference caused by whether ultrasound is performed during the operation. It can be concluded that the coating after ultrasound operation has better electrochemical performance; Figure 4 LiNi 0.83 Mn 0.05 Co 0.12 XRD spectra of samples before and after O2 coating modification; Figure 5 LiNi 0.83 Mn 0.05 Co0.12 TEM spectra of the samples after O2 coating modification, a is the polymer coating, b is LiNi 0.83 Co 0.12 Mn 0.05 O2, coating thickness is 7nm; Figure 6 LiNi 0.83 Mn 0.05 Co 0.12 SEM images of the O2-coated modified samples after cycling at -40°C, a is the uncoated high-nickel ternary positive electrode material, b is the high-nickel ternary positive electrode material after coating with a polymer. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical solution and beneficial technical effect of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and implementation methods. It should be understood that the embodiments described in this specification are only for explaining the present invention, not for limiting the present invention.

[0021] Example 1 Preparation of polypyrrole-coated LiNi 0.83 Mn 0.05 Co 0.12 O2, add polypyrrole to N-methylpyrrolidone, the mass ratio of polypyrrole to N-methylpyrrolidone is 0.5:100, and stir for 30 minutes; take LiNi 0.83 Mn 0.05 Co 0.12 O2 material was added to the solution under ultrasound and ultrasonicated for 30 minutes. The mixed material was placed on a magnetic stirrer for heating and stirring at 60°C for 8 hours at a speed of 650 rpm, and then centrifuged repeatedly to obtain polypyrrole-coated LiNi 0.83 Mn 0.05 Co 0.12 O2, then filtered and washed three times, and placed the polypyrrole-coated ternary material in a vacuum drying oven at 100°C for 14 h, and cooled naturally after heating.

[0022] Making positive electrode: Uncoated LiNi 0.83 Mn 0.05 Co 0.12 LiNi coated with O2 and polypyrrole 0.83 Mn 0.05 Co 0.12O2 is evenly dispersed in N-methylpyrrolidone to prepare a positive electrode slurry, which is coated on a positive electrode current collector and dried, and then cut to obtain a positive electrode sheet, wherein the material composition is 96% of positive electrode material, 2% of positive electrode binder PVDF 5130, and 2% of positive electrode conductor Super P Li.

[0023] The coated samples and uncoated samples were used as positive electrodes, and button batteries assembled with lithium metal as negative electrodes were used. The 0.1C / 1C charge and discharge rates and data were measured in a blue power test cabinet at -40°C. Compared with the uncoated samples, the discharge capacity of the coated samples was significantly improved at low temperatures. Figure 2 The soft-pack battery assembled from the coated samples is shown, and the test conditions are 0.1C / 0.1C and -40°C, indicating that the materials prepared by this method have practical value.

[0024] like Figure 1 As shown, the discharge specific capacity of the high nickel ternary positive electrode coated with polypyrrole is significantly improved compared with the uncoated high nickel ternary positive electrode at -40°C and 1C discharge rate, and the capacity retention rate is as high as 78.36% after 300 cycles.

[0025] like Figure 4 As shown, the diffraction peak positions and intensities are the same, no impurity peaks are detected, and it can be indexed as a typical layered hexagonal α-NaFeO2 structure; the diffraction peaks are obviously split into two pairs, (006) / (012) and (018) / (110), indicating that the layered structure of the high nickel ternary positive electrode material before and after coating with the polymer is well maintained.

[0026] like Figure 5 As shown, the high molecular polymer effectively forms a coating on the surface of the high nickel ternary positive electrode material.

[0027] like Figure 6 As shown, it can be clearly observed that the cracking of the positive electrode particles is effectively reduced when the coated positive electrode material is cycled at low temperature.

[0028] Example 2 Preparation of polypyrrole-coated LiNi 0.83 Mn 0.05 Co 0.12 O2, add polypyrrole to N-methylpyrrolidone according to the chemical dosage ratio and stir for 30 minutes; take LiNi with a mass ratio of 100:1 to polypyrrole 0.83 Mn 0.05 Co 0.12 O2 material, add the solution. The mixed material is placed on a magnetic stirrer and heated and stirred at 60°C for 8 hours, and then centrifuged repeatedly to obtain polypyrrole-coated LiNi 0.83 Mn0.05 Co 0.12 O2, then filtered and washed three times. The polypyrrole-coated ternary material was placed in a vacuum drying oven at 100°C for 14 h, and then cooled naturally after heating.

[0029] Figure 3 The button cell assembled with the sample in Example 2 as the positive electrode and lithium metal as the negative electrode was tested in a blue power test cabinet at a temperature as low as -40°C, and the 0.1C / 1C charge and discharge rate data were compared. The two samples were also coated with LiNi 0.83 Mn 0.05 Co 0.12 O2 materials are differentiated into whether they are treated under ultrasound or not. Figure 3 It shows that the positive electrode material without ultrasonic treatment initially shows a higher discharge capacity, and the cycle performance is lower than that of the positive electrode material treated with ultrasonic treatment, indicating that the coating after ultrasonic operation has better electrochemical performance and limited protection for the positive electrode surface at extremely cold temperatures.

[0030] Example 3 This embodiment provides a high-nickel ternary positive electrode material coated with a polymer, wherein the mass ratio of the coated polymer in step (3) to the high-nickel ternary positive electrode is 0.5:100, and the rest is the same as in embodiment 1.

[0031] Example 4 This embodiment provides a high-nickel ternary positive electrode material coated with a polymer, wherein the mass ratio of the coated polymer in step (3) to the high-nickel ternary positive electrode is 1.5:100, and the rest is the same as in Embodiment 1.

[0032] Example 5 This embodiment provides a high-nickel ternary positive electrode material coated with a polymer, wherein the polymer coated in step (1) is polyaniline, and the rest is the same as in embodiment 1.

[0033] Example 6 This embodiment provides a high-nickel ternary positive electrode material coated with a polymer, wherein the high-nickel ternary positive electrode selected in step (2) is LiNi 0.8 Co 0.15 Al 0.05 O2, the rest is the same as in Example 1.

[0034] Example 7 This embodiment provides a high-nickel ternary positive electrode material coated with a polymer, wherein the stirring speed in step (3) is 600 rpm, and the rest is the same as in Embodiment 1.

[0035] Example 8 This embodiment provides a high-nickel ternary positive electrode material coated with a polymer, wherein the stirring speed in step (3) is 700 rpm, and the rest is the same as in embodiment 1.

[0036] Example 9 This embodiment provides a high-nickel ternary positive electrode material coated with a polymer, wherein the stirring speed in step (3) is 800 rpm, and the rest is the same as in embodiment 1.

[0037] Example 10 This embodiment provides a high-nickel ternary positive electrode material coated with a polymer, wherein the heating temperature in step (3) is 55° C., and the rest is the same as in Embodiment 1.

[0038] Embodiment 11 This embodiment provides a high-nickel ternary positive electrode material coated with a polymer, wherein the heating temperature in step (3) is 65° C., and the rest is the same as in Embodiment 1.

[0039] Example 12 This embodiment provides a high-nickel ternary positive electrode material coated with a polymer, wherein the stirring time in step (3) is 6 hours, and the rest is the same as in embodiment 1.

[0040] Example 13 This embodiment provides a high-nickel ternary positive electrode material coated with a polymer, wherein the stirring time in step (3) is 6.5 hours, and the rest is the same as in embodiment 1.

[0041] Embodiment 14 This embodiment provides a high-nickel ternary positive electrode material coated with a polymer, wherein the stirring time in step (3) is 7 hours, and the rest is the same as in embodiment 1.

[0042] Embodiment 15 This embodiment provides a high-nickel ternary positive electrode material coated with a polymer, wherein the stirring time in step (3) is 7.5 hours, and the rest is the same as in embodiment 1.

[0043] Example 16 This embodiment provides a high-nickel ternary positive electrode material coated with a polymer, wherein the drying temperature in step (3) is 60° C., and the rest is the same as in Embodiment 1.

[0044] Embodiment 17 This embodiment provides a high-nickel ternary positive electrode material coated with a polymer, wherein the drying temperature in step (3) is 70° C., and the rest is the same as in Embodiment 1.

[0045] Embodiment 18 This embodiment provides a high-nickel ternary positive electrode material coated with a polymer, wherein the drying temperature in step (3) is 80° C., and the rest is the same as in Embodiment 1.

[0046] Embodiment 19 This embodiment provides a high-nickel ternary positive electrode material coated with a polymer, wherein the drying temperature in step (3) is 90° C., and the rest is the same as in Embodiment 1.

[0047] Embodiment 20 This embodiment provides a high-nickel ternary positive electrode material coated with a polymer, wherein the drying time in step (3) is 8 hours, and the rest is the same as in embodiment 1.

[0048] Embodiment 21 This embodiment provides a high-nickel ternary positive electrode material coated with a polymer, wherein the drying time in step (3) is 9 hours, and the rest is the same as in embodiment 1.

[0049] Embodiment 22 This embodiment provides a high-nickel ternary positive electrode material coated with a polymer, wherein the drying time in step (3) is 10 hours, and the rest is the same as in embodiment 1.

[0050] Embodiment 23 This embodiment provides a high-nickel ternary positive electrode material coated with a polymer, wherein the drying time in step (3) is 11 hours, and the rest is the same as in embodiment 1.

[0051] Embodiment 24 This embodiment provides a high-nickel ternary positive electrode material coated with a polymer, wherein the drying time in step (3) is 12 hours, and the rest is the same as in embodiment 1.

[0052] Embodiment 25 This embodiment provides a high-nickel ternary positive electrode material coated with a polymer, wherein the drying time in step (3) is 13 hours, and the rest is the same as in embodiment 1.

[0053] In the above embodiments, the organic solvent is one of ethanol, hydroxymethane, N-methyl-2-pyrrolidone, N,N-dimethylformamide, isopropanol and the like; the high molecular polymer is one of polyacrylonitrile, polypyrrole, polyethylene glycol, polyacrylamide, polyacrylic acid and polyacetylene and the like; the high nickel ternary positive electrode material is LiNi x M 1-x-y Co y O2, wherein M is at least one of Al, Mn, Mg, Ti, and W, and x≥0.8, 0<y≤1. They can be replaced with each other.

Claims

1. A method for preparing a high-nickel ternary positive electrode material coated with a polymer, characterized in that: The following steps are involved: (1) Mixing and stirring the polymer and the organic solvent; (2) Slowly add high nickel ternary cathode material powder in ultrasound and continue ultrasound; (3) Using a magnetic stirrer to heat and stir to carry out polymerization; after the polymerization is completed, washing and filtering are performed, and then vacuum drying is performed to obtain a high-nickel ternary positive electrode material coated with a polymer.

2. The method for preparing the high-nickel ternary positive electrode material according to claim 1, characterized in that: The organic solvent in step (1) is one of ethanol, hydroxymethane, N-methyl-2-pyrrolidone, N,N-dimethylformamide, isopropanol and the like.

3. The method for preparing a high-nickel ternary positive electrode material according to claim 1, characterized in that: The high molecular weight polymer in step (1) is one of materials such as polyacrylonitrile, polypyrrole, polyethylene glycol, polyacrylamide, polyacrylic acid and polyacetylene.

4. The method for preparing a high-nickel ternary positive electrode material according to claim 1, characterized in that: The high nickel ternary positive electrode material in step (2) is LiNi x M 1-x-y Co y O2, wherein M is at least one of Al, Mn, Mg, Ti, and W, and x≥0.8, and 0<y≤1.

5. The method for preparing a high-nickel ternary positive electrode material according to claim 1, characterized in that: The duration of ultrasound in step (2) is 10-30 minutes.

6. The method for preparing the high-nickel ternary positive electrode material according to claim 1, characterized in that: In the step (1), the mass of the high molecular weight polymer is 0.5% to 3% of the mass of the organic solution.

7. The method for preparing the high-nickel ternary positive electrode material according to claim 1, characterized in that: The mass of the high molecular weight polymer in step (2) is 0.5% to 5% of the mass of the high nickel ternary positive electrode material.

8. The method for preparing a high-nickel ternary positive electrode material according to claim 7, characterized in that: The mass of the high molecular weight polymer in step (2) is 1.5% to 3% of the mass of the high nickel ternary positive electrode material.

9. The method for preparing a high-nickel ternary positive electrode material according to claim 1, characterized in that: In the step (3), the heating temperature is 50 to 80° C., the rotation speed of the magnetic stirrer is 400 to 1000 rpm, and the stirring time is 6 to 12 hours.

10. The method for preparing a high-nickel ternary positive electrode material according to claim 1, characterized in that: The vacuum drying temperature in step (3) is 60 to 120° C., and the vacuum drying time is 10 to 18 hours.

Citation Information

Patent Citations

  • Nickelic cathode material rich in lithium and preparation method thereof

    CN103825016A

  • Surface treatment method of high-nickel ternary positive electrode material, product and battery

    CN109728277A

  • Novel high-nickel ternary positive electrode material and preparation method thereof

    CN112151792A

  • In-situ oxidative polymerization coated lithium ion ternary cathode material and preparation method thereof

    CN112164775A

  • Conductive polymer coated rubidium-doped high-nickel ternary lithium battery positive electrode material and preparation method thereof

    CN112234203A

Cited By

  • Negative pole piece, preparation method thereof and battery

    CN121964525A